Legislative perceptions of the economic impact of Casper College on the state of Wyoming, Natrona County, and its students: an examination of the reality of those perceptions - Gillum, F. E. "Skip", author; Davies, Timothy Gray, advisor; Bickle, Marianne C., committee member; Jansen, Duane S., committee member; Gloeckner, Gene W., committee member (Colorado State University. Libraries, 2001)
As legislators grapple with funding decisions about state supported programs in difficult financial times, they look to business models that provide data about the positive impacts those programs have on their communities and the state. As the demands for tax dollars become more competitive, it appears that programs with the greatest potential to positively impact the economy will be most favorably received and protected by state policy makers. A prerequisite to gaining legislative support for future higher education funding requests is for colleges to develop data to document the impacts that their schools have on the economies with which they interact. The first purpose of this study was to qualitatively document the perceptions of the Natrona County delegation to the Wyoming State Legislature concerning Casper College's interaction with the earning power of its students and with the state and local economies. The second purpose was to quantitatively document the interactions of Casper College with the same three economies. The third purpose was to compare the qualitative data with the quantitative data to determine any differences. Finally, the study determined the ratio of taxpayer and student support to the economy. The findings indicate that Casper College not only has a positive impact on the state and county economies, but also on the earning power of its students who complete either a certificate or associate degree program of study. Additionally, the findings indicate that the perceptions of the legislators indicate that the college has positive impacts on all three economies. However, their perceptions are anecdotal in nature and appear to be based more on a desire to believe than on solid evidence. They, like most people, want to believe in something as obvious as the value of education. Unfortunately, they were not capable of providing any quantitative data to support their beliefs.
Keywords: higher education